Hyperglycemia in rodent models of type 2 diabetes requires insulin-resistant alpha cells - Lee, Young (Proc Natl Acad Sci U S A, 2014)
To determine the role of glucagon action in diet-induced and genetic type 2 diabetes (T2D), we studied high-fat-diet–induced obese (DIO) and leptin receptor-defective (LepR(−/−)) rodents with and without glucagon receptors (GcgRs). DIO and LepR(−/−),GcgR(+/+) mice both developed hyperinsulinemia, increased liver sterol response element binding protein 1c, and obesity. DIO GcgR(+/+) mice developed mild T2D, whereas LepR(−/−),GcgR(+/+) mice developed severe T2D. High-fat–fed (HFF) glucagon receptor-null mice did not develop hyperinsulinemia, increased liver sterol response element binding protein 1c mRNA, or obesity. Insulin treatment of HFF GcgR(−/−) to simulate HFF-induced hyperinsulinemia caused obesity and mild T2D. LepR(−/−),GcgR(−/−) did not develop hyperinsulinemia or hyperglycemia. Adenoviral delivery of GcgR to GcgR(−/−),LepR(−/−) mice caused the severe hyperinsulinemia and hyperglycemia of LepR(−/−) mice to appear. Spontaneous disappearance of the GcgR transgene abolished the hyperinsulinemia and hyperglycemia. In conclusion, T2D hyperglycemia requires unsuppressible hyperglucagonemia from insulin-resistant α cells and is prevented by glucagon suppression or blockade.